THE STUDY OF A CATALYTIC SYSTEM FOR THE SELECTIVE OXIDATION OF 4-HYDROXYTOLUENE BY OZONE IN THE LIQUID PHASE - ГАЛСТЯН, А. Г.; КРАВЧУК, М. О.; ПАХОМОВА, Д. В. (Technologies and Engineering, 2023)
Purpose. To investigate the peculiarities of the catalytic action of transition metals in combination with mineral acids for the creation of selective syntheses of oxygen-containing derivatives of methylbenzenes by direct oxidation by ozone in the liquid phase. Methodоlogy. A glass column with a porous membrane was used to disperse the gas to establish the kinetic regularities of the reactions of ozone with 4-hydroxytoluene and its acylated derivative. The kinetic parameters of the reaction were studied in a reactor of the "catalytic duck" type, the shaking of which at a speed of 8 oscillations per second provided the kinetic region of the process. The concentration of ozone in the gas phase and the rate constants of its reactions with arenes were determined using the spectrophotometric method of analysis on the SF-46 spectrophotometer. Quantitative content of the reaction mass was recorded by the method of gas-liquid chromatography on the LHM-8MD chromatograph. The concentration of aliphatic peroxides was determined by the method of iodometric titration. Findings. The catalytic reaction of the oxidation of 4-hydroxytoluene by ozone in the liquid phase was studied. It was established that, in the absence of a catalyst, ozonolysis of the aromatic ring with the formation of aliphatic products takes place, and the total yield of oxidation products by the methyl group of the substrate does not exceed 20.5%. Only after adding to the system catalysts based on transition metal salts, it is possible to increase the selectivity and yield of oxidation products by the methyl group up to 77.2%. Under the conditions of the experiment, the main products are 4-acetoxybenzyl acetate (63.2%) and 4-acetoxybenzylidene diacetate (14.0%). It is shown that in the studied system ArCH3-H2SO4-Ас2О-O3, manganese(II) acetate exhibits the greatest catalytic activity, while cobalt salts have practically no catalytic activity under these conditions. Addition of potassium bromide to the oxidation system increases not only the selectivity of oxidation by the methyl group (94.5%), but also the depth of oxidation. The main reaction product is 4-acetoxybenzylidene diacetate (78.0%), which, if necessary, can be easily hydrolyzed to 4-hydroxybenzaldehyde. Originality. The possibility of direct selective oxidation of 4-hydroxytoluene by ozone is shown. Selected catalytic systems that allow stopping the reaction at the stage of formation of the corresponding aromatic alcohol or aldehyde. It was established that the lack of catalytic activity of cobalt(II) acetate under the conditions of the experiment is related to the high reaction rate of reduction of Co(III) to Co(II) in the As2O–H2SO4–O3 system. Practical value. The obtained experimental data are the basis for the creation of environmentally friendly technologies for the synthesis of aromatic alcohols and aldehydes, which are widely used as active pharmaceutical ingredients for the manufacture of medicinal products.